Molecular and functional characterization of the Drosophila melanogaster conserved smORFome. - Bosch, J.A.; Keith, N.; Escobedo, F.; Fisher, W.W.; LaGraff, J.T.; Rabasco, J.; Wan, K.H.; Weiszmann, R.; Hu, Y.; Kondo, S.; Brown, J.B.; Perrimon, N.; et al. (Cell reports, 2023)
Short polypeptides encoded by small open reading frames (smORFs) are ubiquitously found in eukaryotic genomes and are important regulators of physiology, development, and mitochondrial processes. Here, we focus on a subset of 298 smORFs that are evolutionarily conserved between Drosophila melanogaster and humans. Many of these smORFs are conserved broadly in the bilaterian lineage, and ?182 are conserved in plants. We observe remarkably heterogeneous spatial and temporal expression patterns of smORF transcripts-indicating wide-spread tissue-specific and stage-specific mitochondrial architectures. In addition, an analysis of annotated functional domains reveals a predicted enrichment of smORF polypeptides localizing to mitochondria. We conduct an embryonic ribosome profiling experiment and find support for translation of 137 of these smORFs during embryogenesis. We further embark on functional characterization using CRISPR knockout/activation, RNAi knockdown, and cDNA overexpression, revealing diverse phenotypes. This study underscores the importance of identifying smORF function in disease and phenotypic diversity.